Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.436
|View full text |Cite
|
Sign up to set email alerts
|

SlipBuddy: A Mobile Health Intervention to Prevent Overeating

Abstract: Obesity is one of the top health issues around the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…One study to date has utilized machine learning to predict overeating episodes with 71.3% accuracy based on self-reported data of 16 non-treatment-seeking adults with overweight/obesity. 7 The current project sought to replicate and extend this prior work by evaluating an algorithm specifically targeting lapses from a weight loss diet among a treatment-seeking sample. Our methods are novel in that we investigate the utility of combining group- and individual-level data to efficiently generate real-time lapse predictions.…”
mentioning
confidence: 94%
“…One study to date has utilized machine learning to predict overeating episodes with 71.3% accuracy based on self-reported data of 16 non-treatment-seeking adults with overweight/obesity. 7 The current project sought to replicate and extend this prior work by evaluating an algorithm specifically targeting lapses from a weight loss diet among a treatment-seeking sample. Our methods are novel in that we investigate the utility of combining group- and individual-level data to efficiently generate real-time lapse predictions.…”
mentioning
confidence: 94%
“…SlipBuddy was recently developed to inform overeaters of the distinct patterns in their overeating ( Tulu et al., 2017 ). For example, a special, individualized model was developed for one overeater who tended to overeat when she was tired.…”
Section: Discussionmentioning
confidence: 99%
“…There is also mounting evidence that they are effective (Giroux et al, 2017;Haskins et al, 2017;Hester et al, 2005Hester et al, , 2009. Recently, Tulu et al (2017) reported on the effectiveness of an app for overeating. Thomas et al (2011) also reported that 6 months of weekly email contacts plus monthly weight reports from the participants helped speed up weight loss and maintain it.…”
Section: Primary Maintenance Strategiesmentioning
confidence: 99%